Semantic Range of Verb-to-Noun Conversion and Leaners’ Vocabulary Enrichment - Mawarni, Angelina Kusuma Jelita; Bram, Barli (Makassar State University, 2025)
This research explored the semantic range of verb-to-noun conversion in English, centering on how this process, known as nominalization, enhances lexicon and underpins linguistic theory, language education, and computational applications by analyzing 205 verbs and their nominalized shapes extricated from the online Oxford English Dictionary (OED) and online Merriam-Webster Dictionary. The investigation revealed patterns and frequencies of nominalization, categorizing things into semantic types, such as the event, result, agentive, instrumental, locative, and state. The findings revealed that transitive verbs showed the foremost broad semantic extent in nominalization. The semantic range of verb data is 2127 data or 31% per cent which is divided into transitive verb and intransitive verb. The number of semantic ranges in transitive verbs is 1377 data or 20% per cent and the number of semantic ranges in intransitive verbs is 750 data or 11% per cent. While the number of semantic ranges on conversion nouns is 880 data or 13% per cent. A mismatch or unmatched number produced on the semantic range of verb-to-noun was 1268 data or 19% per cent. The implication of this research is to know English learners' awareness of noun-to-verb conversion and ease of communication in daily activities.